Annual Plan Rajasthan 1971-72 - Planning Commission (Planning Commission, 1971)
At the time of formation of the state of Rajasthan, peculiar socio-economic conditions was mainly dependent on the vagaries of monsoon .Until then no coordinated effort had been made to and no incentive for establishment of industrial units were available. No serious attempts were made to Provide basic amenities to the large section of the society. Education and Medical treatment facilities were in a state of great neglect. It is in this background that the State Government Proceeded with the planned Development in the state.
Planning Department, Government of Rajasthan